A New Porcine Animal Model of Cervical Disc Degeneration. (May 2014) - Lee, S. E.; Jahng, T. A.
Introduction: Previous in vivo animal model for disc degeneration was predominantly smaller animals. But such small discs were inappropriate to investigate the cell transplantation therapy highlighted recently. A porcine disc degeneration model in lumbar spine was introduced; however, the lumbar spine was not influenced by the gravity. Hence, the authors performed porcine animal model of disc degeneration in cervical spine. Materials and Methods: Three domestic minipigs (aged, 5 months; weight, 40-50 kg) were used. After anesthesia, right transverse 5 cm-sized incision was made over the three fingers above the clavicle on the anterior neck. Similar to a standard anterior cervical approach of Smith-Robinson method, anatomic dissection was performed to expose anterior surface of the cervical spine. The partial nucleotomy by a Jamshidi bone marrow biopsy needle was performed in one intervertebral disc, and the other disc spaces served as control. Radiologic study using lateral plain radiograph (X-ray) and magnetic resonance image (MRI) was evaluated at preoperation and postoperative 4 and 8 weeks. Results: Two of three minipigs were confirmed disc degeneration at C4-5 and C6-7, respectively. The disc height was reduced by 20% at nucleotomy level. And these discs with previous Pfirrmann grade I were changed to grade IV degeneration at postoperative 4 and 8 weeks. The other disc spaces were maintained previous disc height and Pfirrmann grade I condition. Conclusion: This was a pilot study to introduce a new disc degeneration model with relatively large animal at cervical spine. The authors will conduct a further experiment to confirm the cervical disc degeneration and plan the cell therapy for treatment of disc degeneration. Disclosure of Interest None declared